Traditional clinical symptoms and signs: Kampo pattern diagnosis in modern gastrointestinal disease - Zedler, Paul; Büntzel, Judith; Kuchta, Kenny; Yamaoka, Denichiro; Sato, Nanoha; Watanabe, Kenji; Cameron, Silke (Frontiers in Pharmacology, 2024)
Introduction In traditional Japanese Kampo medicine, a profound anamnesis is completed by clinical examination. The resulting clinical image forms the basis of the patient’s diagnosis pattern, including the recent mental, physical, and social contexts. Kampo questionnaires support pattern diagnosis and bridge traditional and Western medicine diagnoses. Aims of the study Traditional Kampo therapy is tailored to a specific body constitution, while Western medicine treatment is tailored to a specific disease. The aims of this study were to analyze whether traditional Kampo diagnosis is applicable to German patients and whether specific symptom patterns are characteristic for defined diseases. Material and methods This study validates for the first time a Kampo questionnaire adapted for German patients. The analysis focuses on patients with gastrointestinal diseases, the main field for Kampo medicines. Results In total, we prospectively included 251 participants; of those, 58 were cancer patients (23.1%), 35 had Crohn’s disease (13.9%), 18 had ulcerative colitis (7.2%), 17 had irritable bowel syndrome (6.8%), and 103 had other abdominal diseases (41%), as well as 20 German controls (8%). The patient population consisted of 144 female (57.4%) and 107 male (42.6%) participants. The median age was 65 years. The disease duration (average: 211 months) varied from 1 month (cancer patient) to 540 months (patient with Crohn’s disease). The scores for questions on the state of mind were significantly higher in patients with inflammatory bowel disease (IBD) as well as irritable bowel syndrome (IBS)—in comparison to the tumor and control groups. This was reflected in questions about abdominal discomfort, appetite, fecal habits, and cold sensation. Accordingly, symptoms of Qi (i.e., vital energy) deficiency were mostly observed in patients with chronic diseases such as Crohn’s disease and ulcerative colitis. Defined symptom combinations did not reflect conventional Western diagnosis. Conclusion Our study results show that symptom patterns are independent of the underlying disease. They rather depict the individual patient within an individual time frame. Traditional Kampo questionnaires were found to be valid for the analysis of a patients’ body constitution (sho) and serve as a guide for Kampo treatment. We propose that individual pattern diagnosis should be taken into account to help treatment individualization.